2000
DOI: 10.1111/1467-8624.00176
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Security in Infancy and Early Adulthood: A Twenty‐Year Longitudinal Study

Abstract: Sixty white middle-class infants were seen in the Ainsworth Strange Situation at 12 months of age; 50 of these participants (21 males, 29 females) were recontacted 20 years later and interviewed using the Berkeley Adult Attachment Interview (AAI). The interviewers were blind to the participants' Strange Situation classifications. Overall, 72% (36/50) of the infants received the same secure versus insecure attachment classification in early adulthood (kappa = .44, p < .001). As predicted by attachment theory, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
578
1
40

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 926 publications
(655 citation statements)
references
References 10 publications
32
578
1
40
Order By: Relevance
“…Furthermore, consistent with previous research (Waters, Merrick, Treboux, Crowell, & Albersheim, 2000), the parental attachment was positively related to dispositional mindfulness among adolescents. The indirect effect model indicates that the direct effect of parental attachment on PTSD and academic burnout is still significant when mindfulness was inserted into the relation between parental attachment and PTSD and academic.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, consistent with previous research (Waters, Merrick, Treboux, Crowell, & Albersheim, 2000), the parental attachment was positively related to dispositional mindfulness among adolescents. The indirect effect model indicates that the direct effect of parental attachment on PTSD and academic burnout is still significant when mindfulness was inserted into the relation between parental attachment and PTSD and academic.…”
Section: Discussionsupporting
confidence: 89%
“…Advocates of the prototype hypothesis have cited studies that demonstrate stability over long spans of time as evidence for their claims (e.g., Waters, Merrick, et al, 2000). For example, Waters and his colleagues have shown that attachment assessed in infancy predicts attachment assessed at 18 years of age (Waters, Merrick, et al, 2000).…”
Section: Alternative Models Of Stability and Change In Attachmentmentioning
confidence: 99%
“…Insecure avoidant infants explore readily, show little sign of distress when parted from the caregiver, and actively avoid contact upon the caregiver's return. Attachment styles tend to be relatively stable throughout an individual's life, and appear to transmit through generations (Waters, Merrick, Treboux, Crowell, & Albersheim, 2000;Benoit & Parker, 1994). Securely attached children are likely to become autonomous adults, while ambivalent children develop preoccupied or enmeshed adult attachment behaviours, and avoidant infants grow up to be dismissive of attachment.…”
Section: Attachment Theory and Psychosismentioning
confidence: 99%